Molecular Changes in Prepubertal Left Ventricular Development Under Experimental Volume Overload - Hu, Yuqing; Li, Debao; Zhou, Chunxia; Xiao, Yingying; Sun, Sijuan; Jiang, Chuan; Chen, Lijun; Liu, Jinfen; Zhang, Hao; Li, Fen; Hong, Haifa; Ye, Lincai (Frontiers in Cardiovascular Medicine, 2022)
Background Left ventricular (LV) volume overload (VO), commonly found in patients with chronic aortic regurgitation (AR), leads to a series of left ventricular (LV) pathological responses and eventually irreversible LV dysfunction. Recently, questions about the applicability of the guideline for the optimal timing of valvular surgery to correct chronic AR have been raised in regard to both adult and pediatric patients. Understanding how VO regulates postnatal LV development may shed light on the best timing of surgical or drug intervention. Methods and Results Prepubertal LV VO was induced by aortocaval fistula (ACF) on postnatal day 7 (P7) in mice. LV free walls were analyzed on P14 and P21. RNA-sequencing analysis demonstrated that normal (P21_Sham vs.P14_Sham) and VO-influenced (P21_VO vs. P14_VO) LV development shared common terms of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) in the downregulation of cell cycle activities and the upregulation of metabolic and sarcomere maturation. The enriched GO terms associated with cardiac condition were only observed in normal LV development, while the enriched GO terms associated with immune responses were only observed in VO-influenced LV development. These results were further validated by the examination of the markers of cell cycle, maturation, and immune responses. When normal and VO-influenced LVs of P21 were compared, they were different in terms of immune responses, angiogenesis, percentage of Ki67-positive cardiomyocytes, mitochondria number, T-tubule regularity, and sarcomere regularity and length. Conclusions A prepubertal LV VO mouse model was first established. VO has an important influence on LV maturation and development, especially in cardiac conduction, suggesting the requirement of an early correction of AR in pediatric patients. The underlying mechanism may be associated with the activation of immune responses.